Preparation and Evaluation of Classical Ayurvedic Formulation Pathyadikada - Dr. Satish V Kilaje,; Shubham Patil,; Pranil Toraskar,; Pratik Ugare,; Dr. G. Krishnamurthy, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: The objective of this study was to prepare and evaluate Pathyadikada. Methods: The selected formulation Pathyadikada was prepared as per the methodology described in Ayurvedic texts. The prepared and marketed formulations were analyzed for their physico-chemical constants using established methods in accordance with WHO guidelines, the Indian Pharmacopoeia, and standard protocols from the Ayurvedic Pharmacopoeia of India, Herbal Pharmacopoeia, and other relevant sources. Results: A profile consisting of distinguishing parameters was developed to provide means of correct identification. Some important organoleptic features of Pathyadikada laboratory and market formulations like color, odour, taste, appearance, touch, etc. were documented. Physico-chemical constants were determined and documented. The formulations were tested for the presence of heavy metals, microbial content, pesticide residues and aflatoxin, which were also found within the limits of WHO specifications. Preliminary phytochemical studies of Pathyadikada revealed the presence of terpenoids and phenolics as chief constituents. High performance thin-layer chromatography (HPTLC) method was developed and reported for the quantification of Berberine and Quercetin as marker constituents to ensure identity and quality of Pathyadikada. Conclusion: The studies carried out on Pathyadikada can serve as a valuable tool and provide suitable standards for its identification. Phytochemical screening and the quantitative HPTLC assay method developed for quantification of ascorbic acid and gallic acid in Pathyadikada can serve for the routine quality control of commercial samples and help in justifying the traditional claims endowed upon this formulation in a scientifically accepted manner.